The Analisa Kelayakan Usaha Penangkapan Ikan dengan Pole and Line pada KM. Aspac 11 - Suharyanto Suharyanto; Beta Indi; Misbah Sururi; Maqdits Hikmatian; Hendra Poltak (Jurnal Airaha, 2021)
The purpose of this study was to analyze the feasibility level of fishing business with pole and line at KM Aspac 11 operating in WPPNRI 715. The research was carried out on the KM Aspac ship and at the fish landing site from March 2 to May 30, 2020. This type of research is a descriptive study. quantitative. The business feasibility variables analyzed in this study are NPV (Net Present Value), IRR (Internal Rate of Return), and Benefit Cost Ratio (B / C Ratio). The results showed that the fishing effort carried out by KM Aspac 11 in WPPNRI 715 was feasible to run with an NPV value of Rp. 916,444,000, amounting to, an IRR of 28.85, and a B / C Ratio of 1.05.